Global Financial crisis and responses from the GMS countries - Nguyen, Manh Hung (Đại học Kinh tế, 2016)
The recent period has witnessed the remarkable achievements of the Greater Mekong Sub-region (GMS) countries in their economic development and integration which occurred not only at the sub-regional but also at the global level. Nonetheless, the outbreak of theglobal financial crisis, the fluctuation of oil, food, and other commodity prices, and the slowdown of the industrialized economies in 2008 and the early 2009 has brought aboutone of the most difficult challenges to the GMS economies since the Asian financial crisis of 1997 -1998. This article will discuss the impacts of the global financial crisis on the GMS economies andtheir policy responses. Although the economic prospective of the GMS depends heavilyonthe recovery of the global economy, proper policy measures implemented by the governments in the sub-region will contribute a large part to stabilize the market and restore growth